2023
DOI: 10.1101/2023.01.31.526220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep-Learning Assisted, Single-molecule Imaging analysis (Deep-LASI) of multi-color DNA Origami structures

Abstract: Single-molecule experiments have changed the way we investigate the physical world but data analysis is typically time-consuming and prone to human bias. Here, we present Deep-LASI (Deep-Learning Assisted Single-molecule Imaging analysis), a software package consisting of an ensemble of deep neural networks to rapidly analyze single-, two- and three-color single-molecule data, in particular from single-molecule Foerster Resonance Energy Transfer (FRET) experiments. Deep-LASI automatically sorts single molecule… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Considering that protein structure prediction has reached the single-structure frontier 84 , the information from smFRET experiments could leverage the power of artificial intelligence to resolve more complex multi-state and ensemble structural models 83 . Vice versa, the power of artificial intelligence and deep learning can be used to increase the throughput for the design and analysis of smFRET experiments [85][86][87] .…”
Section: Discussionmentioning
confidence: 99%
“…Considering that protein structure prediction has reached the single-structure frontier 84 , the information from smFRET experiments could leverage the power of artificial intelligence to resolve more complex multi-state and ensemble structural models 83 . Vice versa, the power of artificial intelligence and deep learning can be used to increase the throughput for the design and analysis of smFRET experiments [85][86][87] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, from traditional X-ray crystallography or cryo-EM, there are only ~ 200 thousand protein structures shared in the protein data bank (PDB). Specific to DNA nanotechnology, recent studies [28][29][30] showed the DNN is also a great solution for automatically recognizing nanostructure in atomic force microscopy or fluorescence microscopy with high accuracy, which provided a foundation to solving the DNA nanostructure identification problem. However, these works only demonstrated the feasibility of identifying static nanostructures from images and did not address the need for automated property characterization, which is necessary to overcome the characterization bottleneck for dynamic DNA nanodevices.…”
Section: Accelerating the Characterization Of Dynamic Dna Origami Dev...mentioning
confidence: 99%